Ethics of primary health care for children of international origin - Bellver Capella, Vicente (Acta Bioethica, 2012)
Immigration has become an universal phenomenon. One of its effects is the increase in children of international origin in pediatric consultation. This is a doubly vulnerable population, because of being children and because of belonging to cultural contexts foreign to host country. Considering this emergent reality it is essential to question the type of health care they must receive. In the present study, ethical principles for acting are proposed inspired in the main international guidelines about bioethics and children rights: vulnerability principle; respect and love principle; and the principle of access to health care. Finally, some policies that health care managements could implement are proposed to guaranty fair pediatric health care for immigrant children.